You need to find derivative of the given function `y = 5 root(3)((x-1)/(x+1)) ` using chain rule and quotient rule, hence, you do not need to use logarithmic differentiation in this situation since there is no exponent that contains variable x.

You need to convert the cube root into a power such that:

`y = 5*((x-1)/(x+1))^(1/3)`

`(dy)/(dx) = 5*(1/3)*((x-1)/(x+1))^(1/3 - 1)*((x-1)/(x+1))'`

`(dy)/(dx) = 5*(1/3)*((x-1)/(x+1))^(-2/3)*((x-1)'(x+1)-(x-1)(x+1)')/((x+1)^2)`

`(dy)/(dx) = 5*(1/3)*((x-1)/(x+1))^(-2/3)*(x+1-x+1)/((x+1)^2)`

`(dy)/(dx) = 10/(3((x-1)/(x+1))^(2/3)(x+1)^2)`

`(dy)/(dx) = 10/(3root(3)(((x-1)/(x+1))^2)(x+1)^2)`

**Hence, differentiating the given function with respect to x yields `(dy)/(dx) = 10/(3root(3)(((x-1)/(x+1))^2)(x+1)^2).` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now